RUKUN NASUTION (1928-1998) AND HIS POETRY CORPUS: A Preliminary Study - Asari, Hasan; Budianti, Yusnaili (UIN Sumatera Utara, 2024)
Abstract: A corpus of poetry by Rukun Nasution (1928-1998) found in 2018 has not been introduced or studied academically. This study is an initial survey that aimed to introduce the poet called Rukun Nasution and map the corpus of his poetry. Biographical writing methods combined with philology and social history found that Rukun Nasution only received formal education from the People's School (Sekolah Rakyat) for three years. He obtained knowledge mainly through religious non-formal learning forums (majlis ta'lim) and independent reading. Rukun Nasution identified available learning potentials around him and maximized it to advance his education. His poetry's creative dimension was manifested using the aa-aa rhyme, with general Islamic themes. This corpus includes three types: 1) his orinigal compositions; 2) translations from Malay to vernacular Mandailing language; and 3) translation of poetries written in Malay script into Latin script. Rukun Nasution's creativity could be considered unique and extraordinary based on his limited education and external environment. Therefore, his corpus of poetry needs further investigation from philological, linguistic, and historical perspectives and an analysis of its content.Keywords: Islamic poetry, Malay literature, vernacular literature, Rukun Nasution